Epstein Virus Barr-Positive Diffuse Large B-Cell Lymphoma Associated with Hemophagocytic Lymphohistiocytosis. Issue 8 (10th July 2020) - Ricard, Jocelyn A; Charles, River; Tommee, Carolina Gil; Yohe, Sophia; Bell, W Robert; Flanagan, Margaret E
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare and often fatal disease if not diagnosed and treated promptly. HLH can be due to genetic factors or infections, malignancies and collagen-associated vascular diseases. Malignancy-associated HLH is not only more common in the setting of T/NK-cell lymphomas, but may also rarely be seen in the setting of B-cell lymphoma. Here, we describe a unique case of a patient who initially was diagnosed with HLH secondary to Epstein Barr virus (EBV) infection and subsequently developed EBV-positive diffuse large B-cell lymphoma affecting the brain. This case highlights the spectrum of findings associated with EBV infections and the challenges in diagnosing underlying diseases associated with HLH.